Workshop on Visual Data Analysis with R Program - Wutsqa, Dhoriva Urwatul; Kismiantini, Kismiantini; Kusumawati, Rosita; Subekti, Retno; Setiawan, Ezra Putranda; Isnaini, Bayutama; Brilliant, Indira Ihnu (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2024)
Statistics data analysis generally focuses more on mathematical procedures than visual. Visual analysis is very useful for research and this is still very limited to study at Universitas Mercu Buana Yogyakarta, so the UNY Statistics lecturer's service activity is holding visual data analysis workshop with the R program, where this program is open source and is complete for visual analysis. The material for this activity is about procedures and uses for visual data analysis, introduction to the R program, data management with the R program, visual data analysis for group descriptions and comparisons, and visual data analysis for relationships between variables. Evaluation of participants' ability to understand the material is measured through 14 questions with four Likert Scale responses. Based on 40 questionnaires, 27,86% answered "Strongly Agree", 71,96% "Agree", and 0,18% "Disagree" regarding understanding and applying visual data analysis techniques with the R program. Therefore, it can be concluded that the majority of participants could understand the workshop material and follow the training well.